Nanoparticle-enhanced PD-1/PD-L1 targeted combination therapy for triple negative breast cancer - Linde, Caroline; Chien, Yu-Ting; Chen, Zhiqian; Mu, Qingxin (Frontiers in Oncology, 2024)
Breast cancer with triple-negative subtype (TNBC) presents significant challenges with limited treatment options and poorer prognosis than others. While PD-1/PD-L1 checkpoint inhibitors have shown promise, their efficacy in TNBC remains constrained. In recent years, nanoparticle (NP) technologies offer a novel approach to enhance cancer therapy by optimizing the tumor microenvironment and augmenting chemo-and immunotherapy effects in various preclinical and clinical settings. This review discusses recent investigations in NP strategies for improving PD-1/PD-L1 blockade-based combination therapy for TNBC. Those include single or multi-therapeutic NPs designed to enhance immunogenicity of the tumor, induce immunogenic cell death, and target immunosuppressive elements within the tumor microenvironment. The investigations also include NPs co-loaded with PD-L1 inhibitors and other therapeutic agents, leveraging targeted delivery and synergistic effects to maximize efficacy while minimizing systemic toxicity. Overall, NP approaches represent a promising avenue for enhancing PD-1/PD-L1 checkpoint blockade-based combination therapy in TNBC and encourage further developmental studies.